Participatory budgeting in rural councils: The case of Mangwe District council, Zimbabwe - Tambudzai Ndlovu; Gerrit Van der Waldt (Africa’s Public Service Delivery & Performance Review, 2025)
Background: Participatory budgeting (PB) is fundamental to democratic governance and to empowering communities to actively participate in shaping local fiscal decisions. The adoption of PB in Zimbabwe was motivated by the need to enhance citizen participation, improve service delivery, increase transparency and accountability and ensure responsiveness to citizens’ needs.